Covid Conversations 4: Stacy Klein. (November 2021) - Klein, Stacy; Shevtsova, Maria
Abstract : The ecology of the rural setting in which Double Edge Theatre lives and works is as integral to its artistic work as to its principles of social justice, and these qualities mark the ensemble's singular profile not only in the United States but also increasingly on the world theatre map. Stacy Klein co-founded the company in Boston in 1982 as a women's theatre with a defined feminist programme. In 1997, Double Edge moved its work space to a farm that Klein had bought in Ashfield, Massachusetts, commuting from there back to Boston to show its productions. Within a few years, Klein and her collaborators were acutely aware of their separation from the local community, which necessitated a change of perspective to encompass personal and creative engagement with local people and to develop audiences within the area, while not losing sight of their international links. Carlos Uriona, formerly a popular-theatre activist from Argentina, had joined Double Edge and facilitated the local immersion that ultimately became its lifeline, most visibly during the Covid-19 pandemic, as Klein here observes. Klein, who had been a student of Rena Mirecka in Poland (starting in 1976), has maintained her friendship and professional relations with this founding member of the Teatr Laboratorium led by Jerzy Grotowski, inviting Mirecka to run wokshops at the Double Edge Farm. Collaboration with Gardzienice (also from the Grotowski crucible) through the Consortium of Theatre Practices (1999–2001) extended Klein's Polish connections. She expanded her research on community cultures in Eastern and Central Europe and developed these experiences in her probing, distinctly imaginative explorations of theatre-making, while taking a new approach to participatory theatre-making in Ashfield. Her highly visual and sensual compositions are driven by her sense of the fantastic, no more strikingly so than in Klein's Summers Spectacles, which are performed outdoors, in concert with the Farm's natural environment – fields, trees, water, birds, animals, and heaven's firmament. Double Edge's profound commitment in the past decade to what it now terms 'living culture' and 'art justice' has taken root in multiracial collaborations, primarily with the indigenous peoples of Western Massachusetts. This Conversation took place on the winter solstice, 21 December 2020, a date that Maria Shevtsova, Editor of NTQ, had chosen symbolically. It was transcribed by Kunsang Kelden and edited by Shevtsova. Many thanks are extended to Travis Coe of Double Edge for assembling with such loving care the photographs requested.